Bibliometric analysis of research trends and advancements in medicinal plant microbiome - Hu, Danling; Hu, Lizhe; Xiao, Ouli; Chen, Jieyin; Dai, Xiaofeng; Sun, Yongwei; Kong, Zhiqiang (Frontiers in Plant Science, 2024)
Medicinal plants and microorganisms are closely linked, with microorganisms boosting plant growth, offering pest control, and enhancing secondary compound production. However, there's a lack of systematic research, detailed molecular studies, and standardized methods for effectively using microorganisms in developing products from medicinal plants. To enhance understanding of the present research progress, emerging patterns, and key areas pertaining to microorganisms found in medicinal plants, CiteSpace bibliometric software was employed to visualize and analyze 1269 English publications sourced from the Science Net Core Collection database. Through the utilization of keyword co-occurrence analysis and cluster analysis methods, this study seeks to explore collaborative networks among countries, institutions, and scholars involved in the study of microorganisms in medicinal plants.This review highlights key research areas in microbiology, focusing on evaluating natural compounds for antibacterial properties and the impact of secondary metabolites on microbial communities, aiming to highlight significant research domains and primary focuses for researchers and professionals engaged in the field of microbiology concerning medicinal plants.